The Location and Reconstruction of a Byzantine Structure in Marea, Egypt, Including a Comparison of Electronic Remote Sensing and Remote Viewing - Schwartz, Stephan Andrew (Journal of Scientific Exploration, 2019)
This paper reports the location and reconstruction of a Byzantine structure in the now buried city of Marea along the shores of Lake Maryut, some 44 km southwest of Alexandria, Egypt. A Pharonic trade center that was occupied until the 16th Century, the city has been long abandoned and lies buried around what formerly was the lakeshore. This paper reports on an applied Remote Viewing experiment in which two Remote Viewers were asked to first locate Marea, and then a buried building within the city and, finally, to describe what would be found within the building site selected, with a particularly emphasis on tile and other decorative material. It also includes a comparison of Remote Viewing data with electronic remote sensing, and geographical data for the same area done independently three years earlier. The comparison is striking because while the Remote Viewers were successfully able to locate a building, including staking out its door, and corners, as well as providing a wealth of reconstructive and descriptive material about what would be found at the site, the electronic remote sensing and geographical analysis produced no suggestion whatever that there was a site at this location. For this reason, prior to discovery, much of the Remote Viewing data seemed extremely improbable, and notably contradicted the informed judgment of an archaeologist deemed by the University of Alexandria to be the leading authority on Marea. History: The Marea Probe: An Experiment in Applied Parapsychology involving the Location, Reconstruction, and Excavation of a Byzantine Structure - Marea, Egypt. Invited Paper. Annual Meetings of The American Research Center in Egypt. De Young Museum. 14 April 1980. Also presented at the annual meetings of the Parapsychology Association 1980. Proceedings of the Parapsychology Association – 1980.